Two decades of research into SIEs and what do we know? A systematic review of the most influential literature and a proposed research agenda - Brewster, Chris (2021)
Purpose. This paper aims: to undertake a systematic literature review on SIEs, examining twenty years of literature published between 2000 and 2020, focusing on the most-cited empirical work in the field; to analyse the topics covered by these studies; and to propose a research agenda. Methodology. We conducted a systematic literature review, identifying the 20 most-cited empirical articles through citation analysis during the period and, because citations accrue over time, the six most-cited empirical articles of the last three years. We then used content analysis to examine the main themes they address and identify the research gaps. Findings. The most common themes addressed in the SIE literature are: analysis of the types and distinctions of SIEs, motivation to undertake self-initiated expatriation, SIEs' adjustment to the new country, and SIEs' careers and outcomes. Originality. This paper provides a first opportunity to look back at 20 years of research into a relatively new topic, highlighting the main research themes and knowledge gaps, and setting directions for future research. The paper expands knowledge on SIEs, assisting SIE scholars and IHRM practitioners to develop a global, critical understanding of SIEs' issues, and hopefully energising future research in this field.